Vertical Communication on Achievement Motivation and Skills: A Study of Employee's Perspective from A Multi-Level Marketing Company in Bandung, Indonesia - R. Rahadian Arby (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2021)
This study explores the communication aspect further, namely vertical communication related to achievement motivation and skills of employees who work in multi-level marketing companies. The researcher used the SEM PLS analysis technique to determine the effect of vertical communication on achievement motivation and its implications for improving employee skills. The research data use employees who work in multi-level marketing companies in the city of Bandung as many as 53 employees. The study results indicate that there is a significant effect of vertical communication on achievement motivation and has implications for increasing employee skills by 0.177 and 0.610. Furthermore, the study results indicate that more effective vertical communication can increase employee achievement motivation, which can improve employee skills in completing the tasks and responsibilities that the company has given.